The egg characteristics of malon broiler, Japanese quails and their cross (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Sujana E, Anang A, Setiawan I, Widjastuti. 2020. The egg characteristics of malon broiler, Japanese quails and their cross. Biodiversitas 21: 889-895. Research on evaluation of the characteristics of Malon broiler and Japanese quails (Coturnix coturnix japonica) eggs and on the crossbreeding between the two has been implemented in the Quail Breeding Center, Universitas Padjadjaran, Jatinangor, Indonesia. The purpose of this research is to know and evaluate the characteristics of Malon broiler and Japanese quails eggs and the crossbreeding between the two. The research used experimental method with complete random draft consisting of 4 treatments with six repeats, with each replay unit consisting of 10 grains so that the total of incubator eggs used are 240 grains. The treatment used was the breeding or marriage of Malon broiler quail ? x Malon broiler quail ? (MM), selected Japanese quail ? x selected Japanese quail ? (JJ), Malon broiler quail ? x selected Japanese quail ? (MJ), and Japanese selected quail ? x Malon broiler quail ? (JM). Statistical analysis was conducted using GLM (General Linear Model) with test Duncan using SAS application programs. The observed parts are egg weight, egg shape or Shape Index (SI), specific gravity (SG), and eggshell thickness. The results showed a noticeable difference in those parts. Further research results showed that the best quality of egg incubator comes from the crossbreeding of Malon broiler quail ? x selected Japanese quail ?(MJ), which is good for breeding quails.
Keywords: Crossbreeding, eggs characteristics, Malon quail, Japanese quail